Penerapan Awig - Awig dan Pararem dalam Mewujudkan Akuntabilitas Pengelolaan Keuangan pada Dadia Pasek Gelgel Desa Sepang, Kecamatan Busungbiu, Kabupaten Buleleng - Krismayanti, Ni Made Ayu; Atmadja, Anantawikrama Tungga (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This study aims to determine: (1) the background of the application of awig - awig and pararem in Dadia Pasek Gelgel, Sepang Village and (2) financial management accountability with the implementation of awig - awig Â¬ and pararem in Dadia Pasek Gelgel, Sepang Village. Data collection methods were obtained from interviews, observation and documentation conducted at Dadia Pasek Gelgel, Sepang Village, Busungbiu District, and Buleleng Regency. Processing the data that has been collected is then analyzed through data reduction, data presentation and drawing conclusions. The results showed that (1) the application of awig - awig and pararem in dadia Pasek Gelgel Desa Sepang was used as a guide to regulate the most important things in dadia in regulating the ceremony arrangement, ethical procedures and how to deal with problems that exist in dadia Pasek Gelgel and (2) the financial management process of Pasek Gelgel in Sepang Village is carried out in 3 stages, namely planning, implementation and accountability. Accountability of financial management by Prajuru dadia Pasek Gelgel Desa Sepang was carried out by making the LPJ and announced at paruman which coincided with the fifth full moon.